Surface and Size Effects on the Behaviors of Point Defects in Irradiated Crystalline Solids - Ozturk, Abdurrahman; Gencturk, Merve; Ahmed , Karim (Frontiers in Materials, 2021)
We present an elaborate study of the surface and size effects on the transient and steady-state behaviors of point defects in irradiated solids. In this investigation, both pure Ni and binary Ni-Cr were utilized as model systems. We utilize the spatially-resolved rate-theory (SRRT) modeling approach, and directly account for the effects of dose rate, production bias, and defects recombination, reactions with volumetric sinks, and diffusion to surface sinks. Several simulations were conducted to investigate the effects of these parameters in both coupled and decoupled manners. In the presence of production bias, the effects of surface and size persist even as the surface to volume ratio decreases. This was associated with a surface-induced and size-regulated instability. This instability is only triggered above a critical size between 100-500 nm. The critical size decreases with increasing dose rate, increasing production bias, or lowering the temperature. Moreover, this instability results in a pattern that favors the separation of vacancies and interstitials. Once this pattern develops, anomalies in the dependence on size for the transient and steadystate concatenations of point defects and the surface/boundary sink strength are observed. These anomalies tend to render irradiation damage more sever. For pure Ni, it was shown that vacancy supersaturation increases with size, and the rate of increase also rises with size. For the binary Ni-Cr system, it was shown that the magnitude of enrichment/depletion of Ni/Cr at the boundary increases with size, and the width of the enrichment/depletion layer also increases with size. The results obtained here agree well with experimental observations in irradiated materials such as the formation of void denuded zones adjacent to grain boundaries and the size and temperature dependence of the radiation resistance of nanomaterials. The size-dependent behaviors reported here also shed new light on the radiation tolerance of nanomaterials, i.e., the irradiation-induced instabilities are suppressed in such materials. Lastly, the implications of the results obtained here on the development of efficient reduced order models or the utilization of ion irradiation as a surrogate to neutron irradiation are discussed.